A Superacid-catalyzed Synthesis of Fluorescent Covalent Triazine Based Framework Containing Perylene Tetraanhydride Bisimide for Sensing to O-nitrophenol with Ultrahigh Sensitivity. Issue 11 (2nd November 2019) - Geng, Tongmou; Chen, Guofeng; Zhang, Can; Ma, Lanzhen; Zhang, Weiyong; Xia, Hongyu
Abstract: A mesoporous covalent triazine framework, PCPDI, was synthesized via an aromatic nitrile trimerization reaction of N, N′-di(4-cyanphenyl)- 3, 4, 9, 10-tetracarboxydiimide (CPDI ) by CF3 SO3 H catalyzed at 40 °C and this method avoids the use of noble metal catalyzers or high temperature reaction.PCPDI exhibits high thermal stability and strong fluorescence. ThePCPDI shows ultrahigh sensitivity to tracing o-nitrophenol in chloroform withKSV constant of 1.74 × 10 5 L mol −1 and detection limit (LOD ) of 1.72 × 10 −11 mol L −1 .